Redo hepaticojejunostomy in the management of bilioenteric anastomotic strictures - Bharath Kumar Bhat; Samrat Ray; Shailendra Lalwani; Vivek Mangla; Naimish N Mehta; Amitabh Yadav; Samiran Nundy (Current Medicine Research and Practice, 2022)
Background: The Roux-en-Y hepaticojejunostomy (RYHJ) is the commonly done drainage procedure for strictures which occasionally follow operations on the gallbladder and bile ducts. However, 8%–40% of these anastomoses become narrowed again and the redo operation is technically challenging. There are only a few reports which have examined the results of these revision procedures and we therefore decided to analyse our experience of this unusual operation. Aim: To study the role of redo-hepaticojejunostomy in the management of bilio-enteric anastomotic strictures. Materials and Methods: Between January 2010 and January 2016, we performed 23 redo-hepaticojejunostomies for the strictures following an initial hepaticojejunostomy which was done for benign indications in our department and followed them for a minimum of 2 years with clinical, biochemical and radiological tests. Results: There were 7 males and 16 were females who had a median age of 37 years (range 15–63 years). The median interval between the index operation and the stricture recurrence was 10 months. Thirteen (57%) patients underwent initial surgical revision and 10 had the procedure following unsuccessful percutaneous intervention. The median length of hospital stay was 10 days and 21 (91%) only had minor complications. There was no operative mortality. On follow-up of all 23 patients after 2–8 years, six (26%) patients developed stricture recurrence, of whom three were managed with percutaneous dilatation and three required a second revisional surgery. Seventeen patients are symptom-free. Conclusion: Redo RYHJ is a feasible option for strictures following an initial biliary enteric anastomosis with no surgical mortality and three-quarters of the patients being rendered symptom-free.